The Scissors Effect. How structural trends and government intervention are damaging the major European electricity companies and affecting consumers - Robinson, D (Oxford Institute for Energy Studies, 2015)
The major electricity companies (the ‘majors’) in Europe have not recovered from a significant decline in their combined market value that began in early 2008. If the causes are structural, as argued here, these companies may be unable or unwilling to finance the investments required to meet the EU policy goals of energy security, environmental sustainability, and acceptable costs. This research paper by David Robinson argues that the problems facing the European majors reflect a ‘scissors effect’, which has two interpretations. On the one hand, it is a dynamic process whereby certain revenue streams fall, while costs rise, literally cutting profitability. The scissors metaphor extends to a second interpretation: that profitability is being hit – or will be soon – both upstream and downstream. The paper emphasizes underlying structural trends (stagnant demand, decarbonization and more active consumer participation) and government intervention as causes of the scissors effect. Although the structural trends seem now to be irreversible, the future of the sector still depends importantly on government decisions. This paper argues that current electricity regulations and market design are unsustainable. To address this, it is necessary to clarify the respective roles of government and markets and to design regulations and markets for a decarbonized electricity model and for the transition to the new model. Where markets do have a role to play, it is essential that they be left to play that role. The proposal draws on the original spirit of liberalization, but reflects the importance of decarbonization and the technological changes that make active consumer participation in electricity markets a reality. While the majors have to rethink corporate and regulatory strategy, their first priority should be to engage in the debate about the future role of government and competitive markets.